TEORI PARADIGMA NARATIF PADA PENULISAN NASKAH VIDEO ANIMASI EDUKATIF TENTANG PENGENALAN JAMSOSTEK BPJS KETENAGAKERJAAN KEPADA ANAK REMAJA SMP - Nayla Qonita Jasmin; Erna Ernawati; Sutisna Riyanto (Fakultas Ilmu Dakwah dan Komunikasi, 2025)
Visual media can make conveying information easier and more interesting, one of which is by displaying visual media in the form of animated videos. Educational videos with animated visuals are a highly appealing form of media, especially for the younger generation who are accustomed to visual-based content on digital media platforms such as e-learning, YouTube, Instagram, and TikTok. BPJS Ketenagakerjaan is a new innovation in the effort to disseminate educational information on socialization programs to various educational institutions. BPJS Ketenagakerjaan conveys messages to junior high school students depending on how communicators deliver the material and what media is used to deliver the material. Therefore, this study examines how narrative paradigm theory is used in writing educational animated video scripts about introducing BPJS Ketenagakerjaan social security to junior high school students. The narrative paradigm theory is used as the theoretical basis for composing the story in the animated video, emphasizing the importance of narrative in delivering educational messages in animated videos. The implementation of the narrative paradigm in the script is presented to reflect the principles of narrative fidelity and narrative coherence in the story, as well as to build audience understanding and attitude change. The principle of fidelity addresses the social realities of adolescents (concerns about future employment and social protection), while coherence demonstrates relatable elements and reinforces the message about the importance of social security through the experiences of workers.